2021
DOI: 10.1101/2021.08.08.21261763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

T cell responses to SARS-CoV-2 in people with and without neurologic symptoms of long COVID

Abstract: The high prevalence of post-acute sequelae of SARS-CoV-2 infection (PASC) is a significant health concern. In particular, virus-specific immunity in patients who suffer from chronic neurologic symptoms after mild acute COVID remain poorly understood. Here, we report that neuro-PASC patients have a specific signature composed of humoral and cellular immune responses that are biased towards different structural proteins compared to healthy COVID convalescents. Interestingly, the severity of cognitive deficits or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 127 publications
3
42
0
Order By: Relevance
“…The observation of different immunological pro les at the time of hospitalization among patients who exhibited anosognosia of memory functions 69 months after infection supports the hypothesis of indirect CNS damage mediated by immune phenomena 19 , which then fosters the development of longterm cognitive de cits 44,45 . SARS-CoV-2 infection may have induced a different immunological response balance in the group of post-COVID-19 long-term anosognosic patients.…”
Section: Discussionsupporting
confidence: 62%
“…The observation of different immunological pro les at the time of hospitalization among patients who exhibited anosognosia of memory functions 69 months after infection supports the hypothesis of indirect CNS damage mediated by immune phenomena 19 , which then fosters the development of longterm cognitive de cits 44,45 . SARS-CoV-2 infection may have induced a different immunological response balance in the group of post-COVID-19 long-term anosognosic patients.…”
Section: Discussionsupporting
confidence: 62%
“… 4 The naïve CD4+ lymphopenia and the decreased absolute number of Th17 reflect a global defect in the T helper compartment with a reduced viral clearance capacity as was shown in patients with post‐COVID‐19 neurologic symptoms. 5 A low proportion of naïve CD4+ T cells is also associated with a good prognosis in SARS‐CoV‐2 infection, 6 and therefore our data may also reflect the survival status of patients with COVID‐19. It has been suggested that post‐COVID‐19 syndrome shares clinical and immunological features with chronic fatigue syndrome and fibromyalgia, 7 including increased levels of IL‐1β, lower expression of activation markers in T cells and a dysregulated B‐cell compartment.…”
mentioning
confidence: 79%
“…Other studies in mice have demonstrated that poor T cell response underlies severe disease upon SARS-CoV infection 29,30 . T cell dysfunction has also been implicated in poor outcomes in humans infected with SARS-CoV-2 31 . These studies make a strong case for monitoring the T cell clones that respond to vaccines/infections.…”
Section: Discussionmentioning
confidence: 99%